Volcanic Soils as Sources of Novel CO-Oxidizing Paraburkholderia and Burkholderia: Paraburkholderia hiiakae sp. nov., Paraburkholderia metrosideri sp. nov., Paraburkholderia paradisi sp. nov., Paraburkholderia peleae sp. nov., and Burkholderia alpina sp. nov. a Member of the Burkholderia cepacia Complex - Weber, Carolyn F.; King, Gary M. (Frontiers in Microbiology, 2017)
Previous studies showed that members of the Burkholderiales were important in the succession of aerobic, molybdenum-dependent CO oxidizing-bacteria on volcanic soils. During these studies, four isolates were obtained from Kilauea Volcano (Hawai`i, USA); one strain was isolated from Pico de Orizaba (Mexico) during a separate study. Based on 16S rRNA gene sequence similarities, the Pico de Orizaba isolate and the isolates from Kilauea Volcano were provisionally assigned to the genera Burkholderia and Paraburkholderia, respectively. Each of the isolates possessed a form I coxL gene that encoded the catalytic subunit of carbon monoxide dehydrogenase (CODH); none of the most closely related type strains possessed coxL or oxidized CO. Genome sequences for Paraburkholderia type strains facilitated an analysis of 16S rRNA gene sequence similarities and average nucleotide identities (ANI). ANI did not exceed 95% (the recommended cutoff for species differentiation) for any of the pairwise comparisons among 27 reference strains related to the new isolates. However, since the highest 16S rRNA gene sequence similarity among this set of reference strains was 98.93%, DNA-DNA hybridizations (DDH) were performed for two isolates whose 16S rRNA gene sequence similarities with their nearest phylogenetic neighbors were 98.96% and 99.11%. In both cases DDH values were < 16%. Based on multiple variables, four of the isolates represent novel species within the Paraburkholderia: Paraburkholderia hiiakae sp. nov. (type strain I2T = DSM 28029T = LMG 27952T); Paraburkholderia paradisi sp. nov. (type strain WAT = DSM 28027 T = LMG 27949 T); Paraburkholderia peleae sp. nov. (type strain PP52-1T = DSM 28028 T = LMG 27950T); and Paraburkholderia metrosideri sp. nov. (type strain DNBP6-1T = DSM 28030T = LMG 28140T). The remaining isolate represents the first CO-oxidizing member of the Burkholderia cepacia complex: Burkholderia alpina sp. nov. (type strain PO-04-17-38T = DSM 28031T =LMG 28138T).